Bioinspired Color Materials Combining Structural, Dye, and Background Colors. Issue 30 (27th June 2018) - Sakai, Miki; Seki, Takahiro; Takeoka, Yukikazu
Abstract: Human beings have developed many dyes and pigments and use them for printed and display materials to share information. Today's information society is not possible without these color materials. Some living organisms utilize body color for information exchange and protection by skilfully combining dye, structural, and background colors to realize a body color change based on circumstances. In this study, inspired by the extraordinary body color changes of living things, a composite color material combining photochromic dyes, a black substance, a spherical colloidal crystal exhibiting a structural color, and a background color is prepared. In addition to combining a dye color and a structural color that changes upon light irradiation, the contribution of the different effects of the background color on each coloring property allows the construction of a color material that can reversibly change into various colors under different conditions. Abstract : Inspired by the changes of body color of living things, a composite color material combining photochromic dyes, a structural color spherical colloidal crystal, and a background color is presented. The contribution of the different effects of the background color on each coloring property allows the construction of a color material that can reversibly change into various colors under different conditions.